2021
DOI: 10.1021/acs.jpclett.1c01789
|View full text |Cite
|
Sign up to set email alerts
|

Recapture of the Nonvalence Excess Electron into the Excited Valence Orbital Leads to the Chemical Bond Cleavage in the Anion

Abstract: The excess electron in the dipole-bound state (DBS) of the anion is found to be recaptured into the excited valence orbital localized at the positive end of the dipole, leading to the chemical bond cleavage of the anion. In the DBS of the 4-iodophenoxide anion, the extremely loosely bound electron (binding energy of 53 cm −1 ) is recaptured into the πσ* valence orbital, which is repulsive along the C−I bond extension coordinate, leading to the iodide (I − ) and phenoxyl diradical (•C 6 H 4 O•) channel at the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…The DBS at zero-point energy (ZPE) level is located below the electron affinity (EA) threshold whereas additional sharp vibrational Feshbach resonances are above the EA threshold 50 . The DBS at ZPE was found to survive quite long (» ns) 44 , whereas the 11′ 1 mode decays by the autodetachment process with the lifetime of ~33 ps 48 . At the zero-delay time, the non-resonant (791 nm) ps control laser pulse is spatiotemporally overlapped with the scanning pump laser pulse, and all the DBS bands are found to be blue-shifted, indicating that the entire DBS electronic state is lifted up by the amount of the ponderomotive potential given by the control laser pulse intensity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The DBS at zero-point energy (ZPE) level is located below the electron affinity (EA) threshold whereas additional sharp vibrational Feshbach resonances are above the EA threshold 50 . The DBS at ZPE was found to survive quite long (» ns) 44 , whereas the 11′ 1 mode decays by the autodetachment process with the lifetime of ~33 ps 48 . At the zero-delay time, the non-resonant (791 nm) ps control laser pulse is spatiotemporally overlapped with the scanning pump laser pulse, and all the DBS bands are found to be blue-shifted, indicating that the entire DBS electronic state is lifted up by the amount of the ponderomotive potential given by the control laser pulse intensity.…”
Section: Resultsmentioning
confidence: 98%
“…It should be emphasized that the intrinsic nature of the monopole-dipole (or quadrupole) or correlation interaction is anticipated to be little influenced by the molecular complexity 43 , meaning that the ponderomotive force could be effective even for the quite large polyatomic systems as long as the non-valence orbital survives during the oscillating electromagnetic field. It has been recently found that the DBS prepared below the detachment threshold, unlike the Rydberg states of polyatomic molecules, could survive quite long with the lifetime much longer than tens of nanoseconds or microseconds 44 , although it should be noted yet that the NBS lifetime is subject to the detailed electronic structures in terms of the coupling between non-valence and valence orbitals 45 47 . The NBS levels above the detachment threshold mainly decay by the rovibrational autodetachment process.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic nonvalence states are ubiquitous in nature and serve as an effective “doorway” to many important electron-mediated processes including the capture of low-energy electrons, , formation of interstellar species, electron-driven proton transfers, as well as electron transfers in biological systems. The excess electron in nonvalence states can be attached via Rydberg electron transfer to a polar molecule or photoinduced charge-transfer from a nearby valence-bound anion. , The dipole-bound state (DBS) with an excess electron bound to a neutral core via long-range charge–dipole interactions is most commonly observed and has been accessed via resonant photoexcitation of the corresponding valence-bound anion, where the velocity-map imaging (VMI) photoelectron spectroscopy (PES) technique is adopted to probe resonant vibrational autodetachments from the DBS. These studies not only identified specific DBSs and concluded that the electron binding energy (EBE) of a DBS correlates with the neutral dipole moment but also revealed dynamics of various processes associated with DBSs, i.e., autodetachment and internal conversion or intersystem crossing to a valence-bound state. In principle, DBSs should also exist for anionic clusters as long as their corresponding neutral states have a sufficiently large dipole moment. Indeed, such DBSs have been observed and confirmed by Johnson and co-workers in a series of photofragmentation action spectroscopic studies on various solvated halide clusters. , Anionic clusters have long been considered as ideal model systems to mimic chemical and physical processes in bulk and at interfaces .…”
mentioning
confidence: 99%
“…The theoretical requirement for whether a molecule can support a DBS is if |μ| > 1.625 D, although experiments have suggested that the condition is closer to |μ| > 2.0 D due to molecular rotation and centrifugal effects. Despite the DBS lying only 10–100 meV below the detachment threshold, , it has important roles in interstellar anion formation, electron transfer processes in biology, , and coupling of solute molecules with solvated electrons . Recent studies have suggested that DBSs are important in certain isomerization and dissociation reactions. , Underpinning each of these examples are the efficient nonadiabatic couplings that funnel population between the valence-localized and dipole-bound states and interactions with the electronic continuum.…”
mentioning
confidence: 99%